RELATIONSHIP BETWEEN SKALA STROKE GADJAH MADA (SSGM) ON HOSPITAL ADMISSION AND MODIFIED BARTHEL INDEX (MBI) ON DAY OF HOSPITAL DISCHARGE IN RSUP DR. SARDJITO, YOGYAKARTA - , RAYMOND NESAN MARTIN JOSEPH; , Dr.dr.Ismail Setyopranoto, Sp.S(K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: In Indonesia it is reported that at least 50% of the patients treated at the Neurological Ward are stroke patients and 5% of those patients pass away due to stroke. Neurologic deficit which appears among stroke patients have to be assessed quickly, correctly and precisely because the neurologic deficit which appears during the acute stage of stroke can predict the future condition of the stroke patient. Skala Stroke Gadjah Mada (SSGM) is used as a clinical assessment tool to evaluate and monitor the neurological status of a stroke patient, either at the acute stage of stroke or after the stroke attack to evaluate the outcome. Modified Barthel Index (MBI) is used to evaluate the ability of a patient to carry out daily activities because it includes all the components of daily living activities Objective: To determine the relationship between the SSGM score on admission day and Modified Barthel Index (MBI) on day of hospital discharge among acute ischemic stroke patients in RSUP Dr. Sardjito, Yogyakarta. Method: We use cross-sectional study with stroke patient in unit stroke between January until April 2013 as the samples. The data were gathered from medical reports in the Stroke Unit of Dr. Sardjito hospital with number of sample 66 patients. Data gathered were Skala Stroke Gadjah Mada (SSGM) score when admitted to Stroke Unit, Modified Barthel Index (MBI) score on day of hospital discharge, and some of confounding factors. The analysis was done by testing the association between variable groups using chi-square test. Result: Chi-Square test showed that there is significance differences between SSGM score on admission and MBI score on day of hospital discharge with a pvalue of 0.0002 (p<0.05). The higher the SSGM score on admission, the higher the MBI score on day of hospital discharge. This means that patients with severe neurological deficit will have more difficulties to carry out daily living activities. Conclusion: We can conclude that there is a relationship between Skor Stroke Gadjah Mada (SSGM) and Modified Barthel Index (MBI). The higher the SSGM score, the higher the MBI score and the lower the SSGM score, the lower the MBI score.